An Investigation into the Genetic History of Japanese Populations of Three Starfish, Acanthaster planci, Linckia laevigata, and Asterias amurensis, Based on Complete Mitochondrial DNA Sequences. Issue 7 (1st July 2020) - Inoue, Jun; Hisata, Kanako; Yasuda, Nina; Satoh, Noriyuki
Abstract: Crown-of-thorns starfish, Acanthaster planci (COTS), are common in coral reefs of Indo-Pacific Ocean. Since they are highly fecund predators of corals, periodic outbreaks of COTS cause substantial loss of healthy coral reefs. Using complete mitochondrial DNA sequences, we here examined how COTS outbreaks in the Ryukyu Archipelago, Japan are reflected by the profile of their population genetics. Population genetics of the blue starfish, Linckia laevigata, which lives in the Ryukyu Archipelago, but not break out and the northern Pacific sea star, Asterias amurensis, which lives in colder seawater around the main Islands of Japan, were also examined as controls. Our results showed that As. amurensis has at least two local populations that diverged approximately 4.7 million years ago (MYA), and no genetic exchanges have occurred between the populations since then. Linckia laevigata shows two major populations in the Ryukyu Archipelago that likely diverged ∼6.8 MYA. The two populations, each comprised of individuals collected from coast of the Okinawa Island and those from the Ishigaki Island, suggest the presence of two cryptic species in the Ryukyu Archipelago. On the other hand, population genetics of COTS showed a profile quite different from those of Asterias and Linckia . At least five lineages of COTS have arisen since their divergence ∼0.7 MYA, and each of the lineages is present at the Okinawa Island, Miyako Island, and Ishigaki Island. These results suggest that COTS have experienced repeated genetic bottlenecks that may be associated with or caused by repeated outbreaks.